How do monetary incentives affect the measurement of social preferences? - Ernst Fehr; Julien Senn; Thomas Epper; Aljosha Henkel (University of Zurich, Department of Economics, 2025)
In this registered report, we investigate (i) whether incentives affect subjects' willingness to pay to increase, and to decrease the payoff of others, (ii) whether they affect the distribution of social preference types, and (iii) whether they affect the strength and the precision of individuals' structurally estimated social preference parameters. Using an online experiment with a general population sample, we show that the use of monetary incentives, as well as the size of the stakes, have little impact on subjects' modal choices (descriptive analysis), as well as for the distribution of qualitatively distinct preference types in the population (clustering analysis). However, monetary incentives affect quantitative measures of the strength and the precision of social preferences. Indeed, a structural analysis reveals that the preference elicitation with merely hypothetical stakes leads to an overestimation and a less precise measurement of social preferences. Together, these results highlight that incentivizing the elicitation of social preferences is most useful when interested in quantitative estimates. For researchers interested in identifying merely qualitative preferences types, however, hypothetical stakes might suffice.
Keywords: C80; C90; D30; D63; 330; Social Preferences; Altruism; Inequality Aversion; Incentives